Educational and Labor Market Attainments of the 1.5- and Second-Generation Children of East Asian Immigrants in Canada. (May 2016) - Boyd, Monica; Tian, Siyue
Using data from the most recent 2011 Canadian National Household Survey, educational, occupational, and earnings attainments of the East Asian 1.5- and second-generation groups are compared with those of the White third-plus generation. Specific attention is paid to those with both parents born in the People's Republic of China, Hong Kong, Taiwan, Korea, Japan, and in the Southeast Asian country of Vietnam. While East Asian offspring exhibit higher levels of education compared with the white third-plus generation and are more likely to have science and business majors, these more advantageous educational profiles relative to a White majority population do not mask economic inequality, as suggested by the model minority myth. Instead, for most groups a, straightforward model holds, in which higher educational levels and majors usually translate into higher chances of professional employment and higher earnings for the 1.5 and second generations in Canada.